Circulating Apoptotic Microparticles in Systemic Lupus Erythematosus Patients Drive the Activation of Dendritic Cell Subsets and Prime Neutrophils for NETosis. Issue 2 (February 2016) - Dieker, Jürgen; Tel, Jurjen; Pieterse, Elmar; Thielen, Astrid; Rother, Nils; Bakker, Marinka; Fransen, Jaap; Dijkman, Henry B. P. M.; Berden, Jo H.; de Vries, Jolanda M.; Hilbrands, Luuk B.; van der Vlag, Johan
Abstract : Objective: Circulating chromatin‐containing apoptotic material and/or neutrophil extracellular traps (NETs) have been proposed to be an important driving force for the antichromatin autoimmune response in patients with systemic lupus erythematosus (SLE). The aim of this study was to determine the exact nature of microparticles in the circulation of SLE patients and to assess the effects of the microparticles on the immune system. Methods: We analyzed microparticles isolated from the plasma of patients with SLE, rheumatoid arthritis (RA), and systemic sclerosis (SSc), as well as from healthy subjects. The effects of the microparticles on blood‐derived dendritic cells (DCs) and neutrophils were assessed by flow cytometry, enzyme‐linked immunosorbent assay, and immunofluorescence microscopy. Results: In SLE patients, we identified microparticles that were highly positive for annexin V and apoptosis‐modified chromatin that were not present in healthy subjects or in RA or SSc patients. These microparticles were mostly CD31+/CD45– (endothelial), partly CD45+/CD66b+ (granulocyte), and negative for B and T cell markers. Microparticles isolated from the plasma of SLE patients increased the expression of the costimulatory surface molecules CD40, CD80, CD83, and CD86 and the production of proinflammatory cytokines interleukin‐6, tumor necrosis factor, and interferon‐α by blood‐derived plasmacytoid DCs (PDCs) and myeloid DCs (MDCs). SLE microparticles also primed blood‐derived neutrophils for NETosis. Microparticles from healthy subjects and from RA or SSc patients exhibited no significant effects on MDCs, PDCs, and NETosis. Conclusion: Circulating microparticles in SLE patients include a population of apoptotic cell–derived microparticles that has proinflammatory effects on PDCs and MDCs and enhances NETosis. These results underline the important role of apoptotic microparticles in driving the autoimmune response in SLE patients.